The Hidden Diversity of Diatrypaceous Fungi in China - Zhu, Haiyan; Pan, Meng; Wijayawardene, Nalin N.; Jiang, Ning; Ma, Rong; Dai, Dongqin; Tian, Chengming; Fan, Xinlei (Frontiers in Microbiology, 2021)
In this study, we investigated the diversity of diatrypaceous fungi from six regions in China based on morpho-molecular analyses of combined ITS and tub2 gene regions. We accept 23 genera in Diatrypaceae with 18 genera involved in the phylogram, and the other five genera are lack living materials with sequences data. Eleven species included in four genera (viz. Allocryptovalsa, Diatrype, Diatrypella and Eutypella) have been isolated from seven host species, of which nine novel species are included (viz. Allocryptovalsa castanea, A. castaneicola, Diatrype betulae, D. castaneicola, D. quercicola, Diatrypella betulae, Da. betulicola, Da. hubeiensis and Da. shennongensis), a known species of Diatrypella favacea, and a new record of Eutypella citricola from the host genus Morus. Current results show the high diversity of Diatrypaceae which are wood-inhabiting fungi in China.